MATHEMATICAL MODEL OF THE ORGANIZATION OF PASSENGERS’ TRANSPORTATION IN STOPPING-TRANS-RELOCATION POINTS WITH A MULTIPLE CHANGE OF PASSENGER TRAFFIC - M. A. Arslanov; Sh. M. Minatullaev; A. A. Filippov (Вестник СибАДИ, 2018)
Introduction. The article concentrates on the mathematical modeling features of the organization of passengers’ transportations by motor transport in stop-transfer point (STP) with the multiple change of passenger traffic, which is characteristic for resort municipal formations, and also at the organization of sports, cultural and other mass actions.Materials and methods. Materials are presented and a mathematical model is developed, based on the formalization of the STP functioning, as an infrastructural object intended for realization of the transportation process by various types of passenger transport. In addition, compliance with the conditions of the rolling stock rhythmicity on the STP is considered as the basic operating condition.Results. Consequently, the problem of finding the optimal structure and number of bus transport substation units for the STP functioning parameters and the condition for full and timely development of the repeatedly changing passenger flows in it is solved.Discussion and conclusions. The results of mathematical modeling of passengers’ transportations by motor transport allow estimating parameters of functioning of STP and efficiency of management in the conditions of repeatedly changing passenger flows. Therefore, the involvement of additional carriers, flexible planning of routes and schedules according to the regularity of bus traffic, the rhythm of the buses interaction and other types of passenger transport interaction in the STP during peak periods of loading, which ultimately ensures the efficiency and quality of transport services to the population, are considered as control actions.